Sexual Fantasies and Stereotypical Gender Roles: The Influence of Sexual Orientation, Gender and Social Pressure in a Sample of Italian Young-Adults - Tortora, Carla; D’Urso, Giulio; Nimbi, Filippo M.; Pace, Ugo; Marchetti, Daniela; Fontanesi, Lilybeth (Frontiers in Psychology, 2020)
Differences in gender and sexual orientation are suggested to be linked to differences in the way individuals think and behave. The aim of the current study is to evaluate the effect of gender and sexual orientation on sexual fantasies and gender roles in heterosexual and gay and lesbian people. The sample was composed of 547 participants, 246 men (Mage = 28.85; SD = 9,27) and 301 women (Mage = 25,97; SD = 7,141). Within this sample, 61.8% of men and 79.4% of women were heterosexual, whereas 38.2% of men and 20.6% of women were gay and lesbian. Participants completed an online battery of questionnaires to assess their sexual orientation, sexual fantasies, and gender roles on three different dimensions. It was hypothesized that the heterosexual group would report more normative sexual fantasies (H1) and that women in general would report androgynous characteristics, which would be linked to a low degree of reported feminine ideal roles and high social pressure to conform to feminine social expectations (H2). The results showed that lesbian women scored slightly higher than heterosexual women on transgressive sexual fantasies and lower on emotional-romantic ones. Moreover, heterosexual women, but not lesbian women, showed a pattern of high social pressure to conform to feminine expectations together with lower scores in the IRQ. We found the same results on gay men but not for heterosexual men. The overall results suggest that sexual fantasies and gender roles are relatively independent concepts and are influenced by different mechanisms.